If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 300 + -3P = 3P Solving 300 + -3P = 3P Solving for variable 'P'. Move all terms containing P to the left, all other terms to the right. Add '-3P' to each side of the equation. 300 + -3P + -3P = 3P + -3P Combine like terms: -3P + -3P = -6P 300 + -6P = 3P + -3P Combine like terms: 3P + -3P = 0 300 + -6P = 0 Add '-300' to each side of the equation. 300 + -300 + -6P = 0 + -300 Combine like terms: 300 + -300 = 0 0 + -6P = 0 + -300 -6P = 0 + -300 Combine like terms: 0 + -300 = -300 -6P = -300 Divide each side by '-6'. P = 50 Simplifying P = 50
| 3+7(w+7)+w= | | 11x-3x=14 | | 37=5c-8 | | 11x+7+10x=31 | | 3x^2+5x=-4 | | 12x+24=28x-8 | | -34-4x=4x+22 | | 5xy+3x+4y-5xy= | | 5x^4-6x-8=0 | | 57-3x=10x | | 4x+1y=54 | | 2+7x=56 | | 19p+4q-2p-5q= | | 5[y+2]=4-7y | | 66=(2x+3) | | 10x+20= | | 7y-x+10=180 | | y=1.5+5 | | 5x(x+2)-10=14-4x | | 7x-y+10=180 | | -16+6x=-(1-3x) | | .4x-3=.1(x+30) | | -1/2+2= | | (2x-3)(5x+2)= | | 2(0.3+1)=23-0.1r | | 15(8+2c)=15(3c-5) | | 3r-(2r-2)=5-(3-2r) | | 4x^2-27x+49=0 | | -5d(3a+4d-3c)= | | -2-3(4-4x)=50 | | 7x+21=18x+9 | | 27y+2x+7=180 |